Knowledge, Attitudes, and Misconceptions About COVID-19 Prevention Practices Among High and Preparatory School Students in Dessie City, Ethiopia - Feleke A; Adane M; Embrandiri A; Berihun G; Walle Z; Keleb A; Kloos H (Journal of Multidisciplinary Healthcare, 2022)
Alelgne Feleke,1 Metadel Adane,1 Asha Embrandiri,1 Gete Berihun,1 Zebader Walle,2 Awoke Keleb,1 Helmut Kloos3 1Department of Environmental Health, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Public Health, College of Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 3Department of Epidemiology and Biostatistics, University of California, San Francisco, CA, USACorrespondence: Alelgne Feleke; Metadel Adane, Email alelgnefe@gmail.com; metadel.adane2@gmail.comBackground: Knowledge, attitudes, and misconceptions of students about COVID-19 (coronavirus disease) prevention have been examined in relatively few studies. This study aimed to assess the knowledge, attitudes and misconceptions about COVID-19 prevention practices among high and preparatory school (grades 9 to 12) students in Dessie City, Ethiopia.Methods: This school-based cross-sectional study used a pre-tested structured questionnaire and direct observations from March 1 to 30, 2021 in 5 high and preparatory school students in Dessie City, Ethiopia. The sample size was proportionally allocated in each school based on the number of students registered in the first semester, stratified by grade level, and section. Data analysis employed 3 binary logistic regression models (Models I, II and III) with 95% CI (confidence interval). Bivariate analysis (crude odds ratio [COR]) and multivariable analysis (adjusted odds ratio [AOR]) were used. Variables with P-values < 0.3 in the bivariate analysis were retained in the multivariable logistic regression analysis for each model. Variables with significance levels P< 0.05 in the multivariable analysis of each model was identified as significant factors.Results: The levels of good knowledge, positive attitudes, and low misconceptions were 74.8%, 60.2%, and 56.1%, respectively. After adjusting for the covariates, grade 12, positive attitude and living in households with more than 5 members were identified as factors significantly associated with good knowledge about COVID-19 prevention practices. Good knowledge of COVID-19 prevention practices, household size > 5, infection prevention and control (IPC) training, and low level of misconceptions were factors significantly associated with positive attitudes, whereas students age ≥ 18 years, positive attitude, and IPC training were factors significantly associated with less misconceptions about COVID-19 prevention measures.Conclusion: The prevalence of good knowledge, positive attitude, and low level of misconceptions of prevention practices for COVID-19 among students was relatively low. Therefore, Dessie City Health and Education Department and each high and preparatory school should implement continuous monitoring programs to ensure high prevention awareness and promote preventive behavior towards COVID-19.Keywords: COVID-19, knowledge, attitudes, misconceptions, high and preparatory school, students, Dessie City, Ethiopia